ZGORZELSKI’S THEORY OF LYRIC POETRY: GENOLOGY AND AXIOLOGY - KUCZERA-CHACHULSKA, BERNADETTA (Colloquia Litteraria, 2018)
Czesław Zgorzelski is known predominantly as a historian of literature. But Zgorzelski was also a distinguished theoretician of the lyric poetry. His most renowned disciple, Marian Maciejewski, wrote about it in his commentaries to the works of Zgorzelski. Zgorzelski’s works on the lyric poetry contain, very important observations on the nature of the lyric poetry, and the model, gradual changes within this genre. Zgorzelski’s findings in this area are fundamental and can be applied into other non-Romantic areas of reaserch.